Immediate skin-to-skin contact after caesarean section – A simulation study - Leena Taittonen; Tanja Mäkynen; Tiina-Liisa Erkinheimo (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background: Performing a caesarean section using a drape with a transparent window between the mother and the surgical area has not been studied previously. Aim: To describe ways of passing a baby to the mother for skin-to-skin contact after caesarean section, and to analyse the time lapse between cutting the umbilical cord and placement of the baby on the mother. Methods: Simulation characters were used as study subjects. Three methods of passing a baby to the mother for skin-to-skin contact after caesarean section were assessed. In the first method, an opaque drape was placed between the mother and the surgical area, so the mother could not see the baby being born. The surgeon passed the baby to the midwife, who placed the baby on the mother for skin-to-skin contact. In the second method, the mother was able to see the baby being born through a transparent drape. The baby was otherwise handled as in the first method. In the third method, a transparent drape with a window was placed between the mother and the surgical area, so the mother could see the baby being born. The baby was passed through the window in the drape and placed on the mother for skin-to-skin contact. The time lapse between cutting the umbilical cut and skin-to-skin contact was analysed for the three methods. Results: For the first and second methods, the time between cutting the umbilical cord and skin-to-skin contact ranged from 11 to 15.5 s. For the third method, the time was 20–29 s. A minor technical difficulty was noted for the third method. Conclusion: Passing a baby to the mother through a transparent drape with a window after caesarean section is not superior in terms of time, but may improve bonding between the mother and baby.